Foliar Spray of Micronutrients Alleviates Heat and Moisture Stress in Lentil (Lens culinaris Medik) Grown Under Rainfed Field Conditions - Venugopalan, Visha Kumari; Nath, Rajib; Sengupta, Kajal; Pal, Anjan K.; Banerjee, Saon; Banerjee, Purabi; Chandran, Malamal A. Sarath; Roy, Suman; Sharma, Laxmi; Hossain, Akbar; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
The simultaneous occurrence of high temperature and moisture stress during the reproductive stage of lentil (Lens culinaris Medik) constrains yield potential by disrupting the plant defense system. We studied the detrimental outcomes of heat and moisture stress on rainfed lentils under residual moisture in a field experiment conducted on clay loam soil (Aeric Haplaquept) in eastern India from 2018 to 2019 and from 2019 to 2020 in winter seasons. Lentil was sown on two dates (November and December) to expose the later sowing to higher temperatures and moisture stress. Foliar sprays of boron (0.2% B), zinc (0.5% Zn), and iron (0.5% Fe) were applied individually or in combination at the pre-flowering and pod development stages. High temperatures increased malondialdehyde (MDA) content due to membrane degradation and reduced leaf chlorophyll content, net photosynthetic rate, stomatal conductance, water potential, and yield (kg ha–1). The nutrient treatments affected the growth and physiology of stressed lentil plants. The B+Fe treatment outperformed the other nutrient treatments for both sowing dates, increasing peroxidase (POX) and ascorbate peroxidase (APX) activities, chlorophyll content, net photosynthetic rate, stomatal conductance, relative leaf water content (RLWC), seed filling duration, seed growth rate, and yield per hectare. The B+Fe treatment increased seed yield by 35–38% in late-sown lentils (December). In addition, the micronutrient treatments positively impacted physiological responses under heat and moisture stress with B+Fe and B+Fe+Zn alleviating heat and moisture stress-induced perturbations. Moreover, the exogenous nutrients helped in improving physiochemical attributes, such as chlorophyll content, net photosynthetic rate, stomatal conductance, water potential, seed filling duration, and seed growth rate.